2021
DOI: 10.7717/peerj.10572
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity of Escherichia coli from healthy children in rural Gambia

Abstract: Little is known about the genomic diversity of Escherichia coli in healthy children from sub-Saharan Africa, even though this is pertinent to understanding bacterial evolution and ecology and their role in infection. We isolated and whole-genome sequenced up to five colonies of faecal E. coli from 66 asymptomatic children aged three-to-five years in rural Gambia (n = 88 isolates from 21 positive stools). We identified 56 genotypes, with an average of 2.7 genotypes per host. These were spread over 37 seven-alle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…The molecular analysis of the isolates revealed a great variety of strains in all the sampling locations which was also observed in other developing countries (Stoesser et al, 2015;Ramadan et al, 2020;Foster-Nyarko et al, 2021). The majority were from commensal phylogenetic groups A with STc10 being the most frequent clonal complex detected.…”
Section: Discussionsupporting
confidence: 58%
“…The molecular analysis of the isolates revealed a great variety of strains in all the sampling locations which was also observed in other developing countries (Stoesser et al, 2015;Ramadan et al, 2020;Foster-Nyarko et al, 2021). The majority were from commensal phylogenetic groups A with STc10 being the most frequent clonal complex detected.…”
Section: Discussionsupporting
confidence: 58%
“…Epidemiological studies have shown a close genetic relationship between commensal E. coli, APEC and human ExPEC (Foster-Nyarko et al, 2021a). A substantial overlap of phylogenetic groups has been observed between the APEC in this study (A, B1 and unknown) and human ExPEC results (B2 and D) observed from a study by Lee et al, 2016(Lee et al, 2016.…”
Section: Discussionsupporting
confidence: 67%
“…The five genomes are all representatives of the B1 phylotype. E. coli strains belonging to this phylotype have been isolated from the bladders of women with UTI and urge urinary incontinence ( Garretto et al, 2020 ) as well as commensal strains from the human GI tract ( Massot et al, 2016 ; Foster-Nyarko et al, 2021 ) and bovine GI tract ( Arimizu et al, 2019 ). In comparison with other bovine isolates, the bovine urinary isolates are most similar to each other ( Supplementary Figure 1 ), and when compared to human urinary isolates, the core genomes of the five bovine urinary E. coli strains most closely resemble each other ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%